Implementation of Project Based Learning Using Talempong Traditional Musical Instrument Playing to Develop Mutual Cooperation Values in Elementary Schools - Ardipal; Niza Machfauzia, Ayu; Zikri, Ahmad (Universitas Pendidikan Ganesha, 2024)
The need to find an effective method of instilling social values ​​in elementary schools, especially amidst the tendency of individualism. This study aims to evaluate the effect of implementing project-based learning using Talempong games on developing cooperation values ​​among elementary school students. The research method is a quasi-experiment with two groups: an experimental group that received project-based learning with Talempong and a control group that received conventional learning. The research sample consisted of 60 5th-grade students from two elementary schools. The instrument used was a validated questionnaire, and its reliability was measured. Data were analyzed using paired sample t-test and independent sample t-test. The results showed a significant increase in the cooperation value of students in the experimental group, from an average of 3.2 to 4.5, compared to the control group, which only increased from 3.1 to 3.3. This study concludes that implementing project-based learning with Talempong games effectively develops students' cooperation values, and it is recommended to be applied more widely in elementary schools. This research implies that project-based learning with Talempong games can develop students' cooperation values.